Morphoanatomy of Pangasius sp reared in controlled photoperiod - Rienta Bresdo; Eddiwan Eddiwan; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Photoperiod manipulation may affect the morphoanatomy of Pangasius sp. A study aims to determine the effects of photoperiod manipulation on Pangasius sp morphoanatomy has been conducted on July to September 2019. A one factor CRD method with 3 treatments was applied. They were control (12 hours dark and 12 hours light), 18G6T (18 hours dark and 6 hours light) and 24G (24 hours dark). The fish reared for 52 days, they were feed on commercial pellet and were reared in tarp ponds (75 x 50 x 60 cm) that were completed with a water recirculation system. The density of fish was 25 fish/ pond. The fishes were sampled once/14 days, 3 fishes/ treatment. Parameters measured were body length, body weight, condition factor, fish survival, body color, liver condition (color, texture and hepatosomatic index (HSI)), viscerasomatic index (VSI), gonadosomatic index (GSI) and water quality (temperature, pH, DO and ammonia). Results shown that the photoperiod manipulation affects the Pangasius sp morphoanatomy and the 18G6T provided the best result. By the end of the experiment, the fish in this treatment was 186 mm TL, 52 gr BW, 2.7 CF, survival rate was 95%, dark body color, 2.81% HSI and 16.23% VSI.Keywords: Tarp pond, light, IGS, IVS, IHS